Influence of harvesting days and fertilizer levels on agronomic performance and nutritive values of Washo (Loudetia arundinacea) grass (Acta Scientiarum. Animal Sciences, 2025)
This study evaluated the effects of fertilizer levels, harvesting days and cropping years on the agronomic performance and nutritional value of Washo (Loudetia arundinacea) the grass. A 3´3*2 factorial arrangement in a randomized complete block design with three levels of nitrogen fertilizer (75, 100 and 120 Kg), three harvesting days (60, 90 and 120 days) and two cropping years was used. Data on number of tillers (TN), number of leaves (LN), leaf length (LL), plant height (PH), Leaf to stem ratio (LSR), herbage dry matter yield (HDMY), crude protein yield (CPY), nutritional composition, in vitro digestibility were recorded. The results indicated that significantly (p